SYNTAGMATICS ARE THE MAIN FACTOR WHICH MAKES COMMUNICATIVE FUNCTIONS (E Conference Zone, 2022)
This paper discusses and analyzes the concepts of syntagmatics, syntagmatic relations, the semantic properties of lexical units, combinatorics and syntagmatics and proved with the help of examples.